Quantum dots and electroluminescent devices comprising the same

By using the quantum dot of the pillar -phosphopension core and zinc selenium -zinc sulfur shell structure in the electro -littering device, and combined with the zinc metal oxide electronic transmission layer, the problem of insufficient cadmium quantum dot performance is solved, and the high -efficiency photogenic performance is achieved. Glowing and stability.

CN110875433BActive Publication Date: 2025-01-28SAMSUNG ELECTRONICS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN201910813544.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-08-30
Filing Date
2019-08-30
Publication Date
2025-01-28
Estimated Expiration
2039-08-30

AI Technical Summary

Technical Problem

It is difficult to develop quantum dots that do not contain toxic heavy metals such as cadmium, and these quantum dots have insufficient photoluminescence properties and stability in electroluminescent devices.

Method used

The semiconductor nano-crystal core, which includes the tadpole and phosphorus, the first semi-conductor nano-crystal shell with zinc and selenium, and the second semiconductor nano-crystal shell of the zinc and sulfur to the shell to form a quantum dot of the core-shell structure, and Combined with the metal oxide electronic transmission layer containing zinc.

Benefits of technology

Achieving high quantum efficiency (about 9%) and maximum brightness (about 10,000cd/m2), and improved stability, solve the problem of insufficient performance of cadmium -free quantum dots in electrochemical luminous devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN110875433B_ABST
    Figure CN110875433B_ABST
Patent Text Reader

Abstract

Disclosed are quantum dots and an electroluminescent device including the same. The electroluminescent device includes a first electrode and a second electrode facing each other, and an emission layer disposed between the first electrode and the second electrode and including quantum dots. The quantum dots include: a semiconductor nanocrystal core including indium (In) and phosphorus (P); a first semiconductor nanocrystal shell disposed on the semiconductor nanocrystal core, the first semiconductor nanocrystal shell including zinc and selenium; and a second semiconductor nanocrystal shell disposed on the first semiconductor nanocrystal shell, the second semiconductor nanocrystal shell including zinc and sulfur, wherein the quantum dots do not include cadmium. The electroluminescent device has an external quantum efficiency greater than or equal to about 9% and an emission layer greater than or equal to about 10,000 candelas per square meter (cd / m 2 ) at maximum brightness.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to and the benefits of Korean Patent Application No. 10-2018-0102972 filed in the Korean Intellectual Property Office on August 30, 2018, and all rights arising therefrom, the contents of which are incorporated herein by reference in their entirety. Technical Field

[0003] Disclosed are quantum dots and electronic devices (electroluminescent devices) comprising the same. Background Art

[0004] Quantum dots (e.g., semiconductor nanocrystals of nanometer size) with different energy band gaps can be obtained by controlling the size and composition of quantum dots. In colloid synthesis, organic materials such as dispersants can be coordinated during the crystal growth of semiconductor nanocrystals, such as being bonded to the surface of the semiconductor nanocrystals, thereby providing quantum dots with controlled size and showing, for example, luminescent properties. The luminescent properties of quantum dots can be used in various fields. For example, quantum dots can be used in electroluminescent devices, photoluminescent devices, etc. It is desirable to develop environmentally friendly quantum dots that can show, for example, enhanced luminescent properties without toxic heavy metals (e.g., cadmium, mercury, lead, or a combination thereof). Summary of the invention

[0005] One embodiment provides an electroluminescent device including quantum dots having improved photoluminescent properties and enhanced stability.

[0006] One embodiment provides the quantum dots.

[0007] One embodiment provides a method of making the quantum dots.

[0008] One embodiment provides a composition including the quantum dots.

[0009] According to an embodiment, the electroluminescent device comprises:

[0010] a first electrode and a second electrode facing each other, and

[0011] an emission layer disposed between the first electrode and the second electrode, the emission layer comprising quantum dots,

[0012] wherein the quantum dot comprises: a semiconductor nanocrystal core comprising indium (In) and phosphorus (P); a first semiconductor nanocrystal shell disposed on the semiconductor nanocrystal core, the first semiconductor nanocrystal shell comprising zinc and selenium; and a second semiconductor nanocrystal shell disposed on the first semiconductor nanocrystal shell, the second semiconductor nanocrystal shell comprising zinc and sulfur,

[0013] wherein the quantum dots do not include cadmium,

[0014] The electroluminescent device has an external quantum efficiency of greater than or equal to about 9% and a light emission efficiency of greater than or equal to about 10,000 candelas per square meter (cd / m 2 ) at maximum brightness.

[0015] The quantum dots may have a maximum photoluminescence peak in a red light wavelength region.

[0016] The wavelength of the maximum photoluminescence peak of the quantum dots may be greater than or equal to about 600 nanometers (nm) and less than or equal to about 650 nm.

[0017] A difference between a maximum photoluminescence peak wavelength and a first absorption peak wavelength of the quantum dots may be less than or equal to about 20 nm.

[0018] The quantum dots may have an average particle size greater than or equal to about 8 nm.

[0019] The quantum dots may have an average particle size greater than or equal to about 8.5 nm.

[0020] The quantum dots may have an average particle size greater than about 9 nm.

[0021] The quantum dots may have an average particle size greater than about 10 nm.

[0022] The quantum dots may have a quantum yield greater than or equal to about 60%.

[0023] The quantum dots may have a particle size distribution having a standard deviation less than or equal to about 20% of their average size.

[0024] The quantum dots may have a particle size distribution having a standard deviation less than or equal to about 15% of their average size.

[0025] In the quantum dot, a molar ratio of indium to the sum of sulfur and selenium (ie, In:(Se+S), which may be described as a value of In:(Se+S) hereinafter) may be less than or equal to about 0.1:1.

[0026] In the quantum dots, a molar ratio of indium to the sum of sulfur and selenium may be less than or equal to about 0.05:1.

[0027] In the quantum dots, a molar ratio of indium to the sum of sulfur and selenium may be greater than or equal to about 0.02:1.

[0028] In the quantum dots, a molar ratio of sulfur to selenium (S:Se) may be less than or equal to about 4.5:1.

[0029] In the quantum dots, a molar ratio of sulfur to selenium may be greater than or equal to about 0.01:1.

[0030] In the quantum dots, a molar ratio of sulfur to selenium may be greater than or equal to about 0.11:1.

[0031] In the quantum dots, a molar ratio of zinc to indium may be greater than or equal to about 10:1.

[0032] In the quantum dots, a molar ratio of zinc to indium may be greater than or equal to about 15:1.

[0033] In the quantum dots, a molar ratio of zinc to indium may be less than about 52: 1. In the quantum dots, a molar ratio of zinc to indium may be less than or equal to about 49:1.

[0034] The first semiconductor nanocrystal shell may be disposed directly on a surface of the semiconductor nanocrystal core.

[0035] The first semiconductor nanocrystal shell may not include sulfur.

[0036] The first semiconductor nanocrystal shell may have a thickness greater than or equal to about 5 monolayers.

[0037] The first semiconductor nanocrystal shell may have a thickness greater than or equal to about 6 monolayers.

[0038] The first semiconductor nanocrystal shell may have a thickness of less than or equal to about 15 monolayers.

[0039] The second semiconductor nanocrystal shell may be the outermost layer of the quantum dot.

[0040] The second semiconductor nanocrystalline shell may be disposed directly on a surface of the first semiconductor nanocrystalline shell.

[0041] A difference between a maximum photoluminescence peak wavelength and a first absorption peak wavelength of the quantum dots may be less than or equal to about 20 nm (or less than or equal to about 17 nm, or less than or equal to about 16 nm).

[0042] The electroluminescent device may include an electron transport layer between the second electrode and the emission layer.

[0043] The electron transport layer may include a metal oxide including zinc.

[0044] The metal oxide may be Zn 1-x M x O represents, wherein M is Mg, Ca, Zr, W, Li, Ti, Y, Al, or a combination thereof, and 0≤x≤0.5.

[0045] In one embodiment, the above-mentioned quantum dots are provided included in the electroluminescent device.

[0046] The quantum dot includes: a semiconductor nanocrystal core including indium (In) and phosphorus (P); a first semiconductor nanocrystal shell disposed on the semiconductor nanocrystal core, the first semiconductor nanocrystal shell including zinc and selenium; and a second semiconductor nanocrystal shell disposed on the first semiconductor nanocrystal shell, the second semiconductor nanocrystal shell including zinc and sulfur, wherein the quantum dot does not include cadmium, and wherein the difference between the maximum photoluminescence peak wavelength and the first absorption peak wavelength of the quantum dot is less than or equal to about 20 nm.

[0047] The wavelength of the maximum photoluminescence peak of the quantum dots may be greater than or equal to about 600 nm and less than or equal to about 650 nm.

[0048] The quantum dots may have an average particle size greater than or equal to about 8 nm.

[0049] The quantum dots may have an average particle size greater than or equal to about 8.5 nm.

[0050] The quantum dots may have an average particle size greater than about 9 nm.

[0051] The quantum dots may have an average particle size greater than about 10 nm.

[0052] The quantum dots may have a particle size distribution having a standard deviation less than or equal to about 20% of their average size.

[0053] The quantum dots may have a quantum yield greater than or equal to about 60%.

[0054] The half width of the maximum photoluminescence peak of the quantum dots may be less than or equal to about 40 nm.

[0055] The first semiconductor nanocrystal shell may be disposed directly on a surface of the semiconductor nanocrystal core, the first semiconductor nanocrystal shell may not include sulfur, and the second semiconductor nanocrystal shell may be an outermost layer of the quantum dot.

[0056] In the quantum dot, a molar ratio of indium to the sum of sulfur and selenium (ie, In:(Se+S), which may be described as a value of In:(Se+S) hereinafter) may be less than 0.1:1.

[0057] In the quantum dots, a molar ratio of indium to the sum of sulfur and selenium may be greater than or equal to about 0.02:1.

[0058] In the quantum dots, a molar ratio of zinc to indium may be greater than or equal to about 10:1.

[0059] In the quantum dots, a molar ratio of zinc to indium may be less than about 52:1.

[0060] The first semiconductor nanocrystal shell may have a thickness of greater than or equal to about 6 monolayers, greater than or equal to about 7 monolayers, greater than or equal to about 8 monolayers, greater than or equal to about 9 monolayers, or greater than or equal to about 10 monolayers.

[0061] A difference between a maximum photoluminescence peak wavelength and a first absorption peak wavelength of the quantum dots may be less than or equal to about 17 nm (or less than or equal to about 16 nm).

[0062] In other embodiments, the quantum dots include:

[0063] A semiconductor nanocrystal core comprising indium and phosphorus,

[0064] a first semiconductor nanocrystal shell disposed on the semiconductor nanocrystal core, the first semiconductor nanocrystal shell comprising zinc and selenium, and

[0065] a second semiconductor nanocrystalline shell disposed on the first semiconductor nanocrystalline shell, the second semiconductor nanocrystalline shell comprising zinc and sulfur,

[0066] wherein in the quantum dot, a molar ratio of indium to the sum of sulfur and selenium, In:(Se+S), is greater than or equal to about 0.02:1 and less than or equal to about 0.1:1,

[0067] wherein the quantum dots do not include cadmium, and

[0068] The average particle size of the quantum dots is greater than or equal to about 8 nanometers and less than or equal to about 50 nm.

[0069] In one embodiment, a composition is provided that may include an organic solvent and the cadmium-free quantum dots described above.

[0070] The electroluminescent device of the embodiment is based on, for example, including environmentally friendly quantum dots, and may exhibit, for example, enhanced electroluminescent properties (eg, improved external quantum efficiency (EQE) and increased maximum brightness) and improved stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0071] The above and other advantages and features of the present disclosure will become more apparent by further describing exemplary embodiments thereof in detail with reference to the accompanying drawings, in which:

[0072] Figure 1 is a schematic cross-sectional view of a quantum dot light emitting diode (QD LED) device according to an embodiment.

[0073] Figure 2 Schematic cross-sectional view of a QD LED device according to one embodiment.

[0074] Figure 3Schematic cross-sectional view of a QD LED device according to one embodiment.

[0075] Figure 4 The UV-Vis absorption spectrum (dashed line) and photoluminescence spectrum (solid line) of the quantum dots prepared in Example 1 are shown.

[0076] Figure 5 Graph of external quantum efficiency (EQE) (percent (%)) versus voltage (volt (V)) for the device prepared in Example 4.

[0077] Figure 6 EQE (percentage (%)) versus luminance (L) (cd / m2) of the device prepared in Example 4 2 ))'s picture. DETAILED DESCRIPTION

[0078] Hereinafter, example embodiments of the present disclosure will be described in detail so that those skilled in the art will understand it. However, the present disclosure may be embodied in many different forms and is not to be construed as limited to the example embodiments set forth herein.

[0079] In the accompanying drawings, the thickness of layers, films, panels, regions, etc., is exaggerated for clarity. In the specification, the same reference numerals always represent the same elements. It will be understood that when an element such as a layer, film, region, or substrate is referred to as being "on" another element, it can be directly on the other element or there can be intermediate elements. On the contrary, when an element is referred to as being "directly on" another element, there are no intermediate elements.

[0080] It will be understood that although the terms "first", "second", "third", etc. may be used herein to describe a variety of elements, components, regions, layers and / or parts, these elements, components, regions, layers and / or parts should not be limited by these terms. These terms are only used to distinguish one element, component, region, layer or part from another element, component, region, layer or part. Therefore, without departing from the teachings herein, the "first element", "component", "region", "layer" or "part" discussed below may be referred to as a second element, component, region, layer or part.

[0081] The terms used herein are only for the purpose of describing specific embodiments and are not intended to be restrictive. As used herein, the singular forms "one (kind)" and "the (said)" are intended to include plural forms, including "at least one (kind)", unless the content clearly indicates otherwise. "At least one (kind)" will not be interpreted as limiting "one" or "a kind". "Or" means "and / or". As used herein, the term "and / or" includes any and all combinations of one or more of the relevant enumerated items. It will be further understood that the term "include" or "comprising" when used in this specification indicates that there are stated features, regions, wholes, steps, operations, elements, and / or components, but does not exclude the presence or addition of one or more other features, regions, wholes, steps, operations, elements, components, and / or their collections.

[0082] As used herein, "about" includes the stated value and means within an acceptable range of deviation for the particular value as determined by one of ordinary skill in the art taking into account the measurement in question and the errors associated with the measurement of the particular quantity (i.e., the limitations of the measurement system). For example, "about" may mean that the deviation from the stated value is within one or more standard deviations, or within a range of ±10% or 5%.

[0083] Unless otherwise defined, all terms (including technical and scientific terms) used in this article have the same meaning as commonly understood by ordinary technicians in the field to which the present disclosure belongs. It will be further understood that terms, such as those defined in commonly used dictionaries, should be interpreted as their meanings consistent with their meanings in the context of the present disclosure and the relevant art, and will not be interpreted in an idealized or overly formal sense unless clearly defined in this article.

[0084] Exemplary embodiments are described herein with reference to cross-sectional views as schematic diagrams of idealized embodiments. Thus, variations in the shape of the figures as a result of, for example, manufacturing techniques and / or tolerances are anticipated. Therefore, the embodiments described herein should not be construed as being limited to the specific shapes of the regions as shown herein, but rather include deviations in shape caused by, for example, manufacturing. For example, a region illustrated or described as flat may typically have rough and / or nonlinear features. In addition, the illustrated sharp corners may be rounded. Therefore, the regions shown in the figures are schematic in nature, and their shapes are not intended to illustrate the precise shapes of the regions and are not intended to limit the scope of the claims.

[0085] As used herein, a work function or energy level (e.g., a highest occupied molecular orbital (HOMO) energy level or a lowest unoccupied molecular orbital (LUMO) energy level) is expressed as an absolute value from a vacuum energy level. In addition, when a work function or energy level is referred to as "deep", "high", or "large", the work function or energy level has a large absolute value based on a vacuum energy level of "0 eV", and when a work function or energy level is referred to as "shallow", "low", or "small", the work function or energy level has a small absolute value based on a vacuum energy level of "0 eV".

[0086] As used herein, the term "Group" may refer to a Group of the periodic table.

[0087] As used herein, “Group I” may refer to Group IA and Group IB, and examples may include Li, Na, K, Rb, and Cs, but are not limited thereto.

[0088] As used herein, “Group II” may refer to Group IIA and Group IIB, and examples of Group II metals may be Cd, Zn, Hg, and Mg, but are not limited thereto.

[0089] As used herein, “Group III” may refer to Group IIIA and Group IIIB, and examples of Group III metals may be Al, In, Ga, and Tl, but are not limited thereto.

[0090] As used herein, "Group IV" may refer to Group IVA and Group IVB and examples of Group IV metals may be Si, Ge, and Sn, but are not limited thereto. As used herein, the term "metal" may include semimetals such as Si.

[0091] As used herein, “Group V” may refer to Group VA, and examples may include nitrogen, phosphorus, arsenic, antimony, and bismuth, but are not limited thereto.

[0092] As used herein, "Group VI" may refer to Group VIA, and examples may include sulfur, selenium, and tellurium, but are not limited thereto.

[0093] As used herein, when no definition is otherwise provided, "substituted" refers to a compound, group, or moiety in which hydrogen is replaced by a C1-C30 alkyl, C2-C30 alkenyl, C2-C30 alkynyl, C2-C30 epoxy, C2-C30 alkyl ester, C3-C30 alkenyl ester (e.g., acrylate, methacrylate), C6-C30 aryl, C7-C30 alkylaryl, C1-C30 alkoxy, C1-C30 heteroalkyl, C3-C40 heteroaryl, C3-C30 heteroalkylaryl, C3-C30 cycloalkyl, C3-C15 cycloalkenyl, C6-C30 cycloalkynyl, C2-C30 heterocycloalkyl, halogen (-F, -Cl, -Br, or -I), hydroxyl (-OH), nitro (-NO), or a combination thereof. 2 ), thiocyanate (-SCN), cyano (-CN), amino (-NRR', wherein R and R' are independently hydrogen or C1-C6 alkyl), azido (-N 3 ), amidino (-C(=NH)NH 2 ), hydrazino (-NHNH 2 ), hydrazone (=N(NH 2 )), aldehyde group (-C(=O)H), carbamoyl group (-C(O)NH 2 ), thiol group (-SH), ester group (RC(=O)O- or -C(=O)OR, wherein R is C1-C6 alkyl or C6-C12 aryl), carboxyl group (-COOH) or its salt (-C(=O)OM, wherein M is an organic or inorganic cation), sulfonic acid group (-SO 3 H) or its salt (-SO 3 M, where M is an organic or inorganic cation), a phosphate group (-PO 3 H 2 ) or its salt (-PO 3 MH or -PO 3 M 2 , wherein M is an organic or inorganic cation), or a combination thereof.

[0094] As used herein, when no definition is otherwise provided, the term "hydrocarbyl" refers to a group including carbon and hydrogen (e.g., alkyl, alkenyl, alkynyl, aryl, etc.). The hydrocarbyl group may be a group having a valence of at least 1 formed by removing at least one hydrogen from an alkane, an alkene, an alkyne, an aromatic hydrocarbon, etc. At least one methylene group in the hydrocarbyl group may be replaced by an oxygen moiety (-O-), a carbonyl moiety, an ester moiety (-C(=O)O-), -NH-, or a combination thereof.

[0095] As used herein, when a definition is not otherwise provided, an "aliphatic group" refers to a C1-C40 linear or branched hydrocarbon group (eg, an alkyl group, an alkenyl group, or an alkynyl group).

[0096] As used herein, when a definition is not otherwise provided, "alkoxy" refers to an alkyl group linked through an oxygen group (ie, alkyl-O-), for example, methoxy, ethoxy, and sec-butoxy.

[0097] As used herein, when a definition is not otherwise provided, "alkyl" refers to a linear or branched saturated monovalent (eg, C1-C40) hydrocarbon group (eg, methyl or hexyl).

[0098] As used herein, when a definition is not otherwise provided, "alkylene" refers to a linear or branched saturated (eg, C2-C40) aliphatic hydrocarbon group having a valence of at least 2 and optionally substituted with at least one substituent.

[0099] As used herein, when a definition is not otherwise provided, "alkynyl" refers to a straight or branched monovalent (eg, C2-C40) hydrocarbon group (eg, ethynyl) having at least one carbon-carbon triple bond.

[0100] As used herein, when no definition is otherwise provided, "aromatic" refers to an organic compound or group that includes at least one unsaturated cyclic group having delocalized π electrons. The term encompasses both aromatic hydrocarbon compounds and heteroaromatic compounds.

[0101] As used herein, when no definition is otherwise provided, "aryl" refers to a hydrocarbon group having a valence of at least 1, such as formed by removing at least one hydrogen atom from one or more rings of an aromatic hydrocarbon (eg, phenyl or naphthyl).

[0102] As used herein, when no definition is otherwise provided, the term "hetero" refers to including at least one (e.g., one to three) heteroatom, wherein the heteroatom may be N, O, S, Si, or P, preferably N, O, or S.

[0103] As used herein, when no definition is otherwise provided, an "amine" group has the general formula -NRR, wherein each R is independently hydrogen, C1-C40 alkyl, C7-C40 alkylaryl, C7-C40 arylalkyl, or C6-C40 aryl.

[0104] As used herein, when no definition is otherwise provided, "aromatic hydrocarbons" refer to hydrocarbons having an aromatic ring, and include monocyclic and polycyclic hydrocarbons, wherein the additional rings of the polycyclic hydrocarbons may be aromatic or non-aromatic. Specific examples of aromatic hydrocarbons include benzene, naphthalene, toluene, and xylene.

[0105] As used herein, when a definition is not otherwise provided, "arylalkyl" refers to a substituted or unsubstituted aryl group covalently linked to an alkyl group attached to the compound (eg, benzyl is a C7 arylalkyl group).

[0106] As used herein, when no definition is otherwise provided, "heteroaryl" refers to an aromatic group that includes at least one heteroatom covalently bonded to one or more carbon atoms in the aromatic ring.

[0107] As used herein, the average size of particles (or quantum dots) can be determined by using electron microscopy analysis and optionally a commercially available image analysis program (Image J). The average can be the mean or median.

[0108] Hereinafter, a light emitting device according to an embodiment is described with reference to the accompanying drawings.

[0109] Figure 1 is a schematic cross-sectional view of an electroluminescent device (hereinafter, also referred to as a light emitting device) according to an embodiment.

[0110] Reference Figure 1 The light emitting device 10 according to the embodiment includes a first electrode 11 and a second electrode 15 facing each other, and an emission layer 13 disposed between the first electrode 11 and the second electrode 15 and including quantum dots. The hole auxiliary layer 12 may be disposed between the first electrode 11 and the emission layer 13, and the electron auxiliary layer 14 may be disposed between the second electrode 15 and the emission layer 13.

[0111] The device may further include a substrate. The substrate may be disposed on a major surface (e.g., a lower surface) of the first electrode 11 or on a major surface (e.g., an upper surface) of the second electrode 15. In one embodiment, the substrate may be disposed on a major surface (e.g., a lower surface) of the first electrode. The substrate may be a substrate including an insulating material (e.g., an insulating transparent substrate). The substrate may include glass; polymers such as polyesters (e.g., polyethylene terephthalate (PET), polyethylene naphthalate (PEN)), polycarbonates, polyacrylates, polyimides, polyamide-imides, or combinations thereof; polysiloxanes (e.g., PDMS); inorganic materials such as Al 2 O 3 , ZnO, or a combination thereof; or a combination thereof, but not limited thereto. The substrate may be made of a silicon wafer. Here, "transparent" may refer to the following situation: the substrate has a transmittance greater than or equal to about 85%, such as greater than or equal to about 88%, greater than or equal to about 90%, greater than or equal to about 95%, greater than or equal to about 97%, or greater than or equal to about 99% for light of a predetermined wavelength (e.g., light emitted from the quantum dots). The thickness of the substrate may be appropriately selected in consideration of the substrate material, but is not particularly limited. The transparent substrate may be flexible. The substrate may be omitted.

[0112] One of the first electrode 11 and the second electrode 15 may be an anode and the other may be a cathode. For example, the first electrode 11 may be an anode and the second electrode 15 may be a cathode.

[0113] The first electrode 11 may be made of a conductor such as a metal, a conductive metal oxide, or a combination thereof. The first electrode 11 may be made of, for example, a metal or an alloy thereof, such as nickel, platinum, vanadium, chromium, copper, zinc, or gold; a conductive metal oxide such as zinc oxide, indium oxide, tin oxide, indium tin oxide (ITO), indium zinc oxide (IZO), or fluorine-doped tin oxide; or a combination of a metal and a metal oxide such as ZnO and Al, or SnO 2 In one embodiment, the first electrode may include a transparent conductive metal oxide such as indium tin oxide. The work function of the first electrode may be higher than the work function of the second electrode to be described later. The work function of the first electrode may be lower than the work function of the second electrode.

[0114] The second electrode 15 can be made of a conductor such as a metal, a conductive metal oxide, a conductive polymer, or a combination thereof. The second electrode 15 can be made of, for example, a metal or an alloy thereof, such as aluminum, magnesium, calcium, sodium, potassium, titanium, indium, yttrium, lithium, gadolinium, silver, tin, lead, cesium, or barium; or a multilayer structure of a material such as LiF / Al, Li 2 O / Al, Liq / Al, LiF / Ca, or BaF 2 / Ca, but not limited thereto. The conductive metal oxide is the same as described above.

[0115] The work function of the first electrode may be higher than the work function of the second electrode. The work function of the first electrode may be lower than the work function of the second electrode.

[0116] In one embodiment, the work function of the first electrode 11 may be about 4.5 electron volts (eV) to about 5.0 eV (e.g., about 4.6 eV to about 4.9 eV). The work function of the second electrode 15 may be greater than or equal to about 4.0 eV and less than about 4.5 eV (e.g., about 4.0 eV to about 4.3 eV).

[0117] In one embodiment, the work function of the second electrode 15 may be about 4.5 eV to about 5.0 eV (eg, about 4.6 eV to about 4.9 eV). The work function of the first electrode 11 may be greater than or equal to about 4.0 eV and less than about 4.5 eV (eg, about 4.0 eV to about 4.3 eV).

[0118] The first electrode 11, the second electrode 15, or a combination thereof may be a light-transmitting electrode and the light-transmitting electrode may be made of, for example, a conductive oxide such as zinc oxide, indium oxide, tin oxide, indium tin oxide (ITO), indium zinc oxide (IZO), or fluorine-doped tin oxide, or a single or multiple metal thin layer. When one of the first electrode 11 and the second electrode 15 is a non-light-transmitting electrode, the non-light-transmitting electrode may be made of, for example, an opaque conductor such as aluminum (Al), silver (Ag), or gold (Au).

[0119] The thickness of the electrode (the first electrode, the second electrode, or a combination thereof) is not particularly limited and may be appropriately selected in consideration of device efficiency. For example, the thickness of the electrode may be greater than or equal to about 5 nm, for example, greater than or equal to about 50 nm. For example, the thickness of the electrode may be less than or equal to about 100 micrometers (μm), for example, less than or equal to about 10 μm, less than or equal to about 1 μm, less than or equal to about 900 nm, less than or equal to about 500 nm, or less than or equal to about 100 nm.

[0120] The emission layer 13 includes (e.g., multiple) quantum dots. Quantum dots (hereinafter, also referred to as semiconductor nanocrystals) can absorb light from an excitation source and be excited and can emit energy (light of a wavelength) corresponding to the energy band gap of the quantum dots. The energy band gap of the quantum dots can vary with the size and composition of the semiconductor nanocrystals. For example, as the size of the quantum dots increases, the quantum dots can have a narrower energy band gap, thereby having an increased emission wavelength. Semiconductor nanocrystals can be used as luminescent materials in a variety of fields such as display devices, energy devices, or bioluminescent devices.

[0121] Quantum dots with photoluminescence (PL) properties at applicable levels may include cadmium (Cd). Cadmium may cause environmental / health problems and is one of the elements restricted by the Restriction of Hazardous Substances Directive (RoHS) in many countries. Compared with cadmium-based quantum dots, cadmium-free quantum dots may exhibit low electroluminescent properties and poor stability. Therefore, it is desirable to develop cadmium-free semiconductor nanocrystal particles and electroluminescent devices including them with improved photoluminescent properties (e.g., reduced half width (FWHM), improved EQE, improved brightness, etc.). For example, in order to realize QD LED devices (i.e., display devices without light sources), quantum dots that can emit red light and are environmentally friendly and exhibit enhanced electroluminescent properties are necessary. Although quantum dots based on indium phosphide (InP) are a type of cadmium-free and red-emitting quantum dots, quantum dots based on indium phosphide may exhibit insufficient levels of electroluminescent properties. For example, quantum dots based on indium phosphide and emitting red light may exhibit an EQE of less than or equal to about 2.5%. Furthermore, the stability (eg, lifetime) of cadmium-free quantum dots that emit red light may not be easily improved.

[0122] The inventors have discovered that quantum dots having the features described herein can exhibit improved electroluminescent properties. The inventors have also discovered that the quantum dots can exhibit improved properties in electroluminescent devices (if desired, when the quantum dots are combined with a zinc metal oxide-based electron transport layer to be described below). By controlling the preparation conditions (e.g., controlling factors that can affect the growth rate of the core, shell, or combination thereof, such as reaction temperature, injection rate of precursors, type and amount of precursors, or a combination thereof), the quantum dots included in the device of the embodiment can have a size, composition, property (e.g., Stokes shift), or a combination thereof to be described below. When the quantum dots of the embodiment are combined with an inorganic electronic auxiliary layer (e.g., ETL) comprising a metal oxide containing zinc, such as zinc oxide, zinc magnesium oxide, etc., the quantum dots can exhibit high EQE and high brightness (e.g., EQE greater than or equal to about 9% and greater than or equal to about 10,000 cd / m 2 For red-emitting electroluminescent devices based on cadmium-free quantum dots, it may be desirable to improve both EQE and brightness. In addition, devices including quantum dots of embodiments may exhibit improved stability.

[0123] Therefore, one embodiment relates to quantum dots (or quantum dot populations) as described in detail below. The quantum dots of the embodiments do not include cadmium. The quantum dots of the embodiments may not include toxic heavy metals such as cadmium, mercury, lead, or combinations thereof.

[0124] The quantum dot includes a semiconductor nanocrystal core including indium (In) and phosphorus (P), a first semiconductor nanocrystal shell disposed on the semiconductor nanocrystal core and including zinc and selenium, and a second semiconductor nanocrystal shell disposed on the first semiconductor nanocrystal shell and including zinc and sulfur.

[0125] The quantum dots may have a maximum photoluminescence peak in a red light wavelength region. The quantum dots may have a maximum photoluminescence peak in a green light wavelength region.

[0126] When the quantum dot emits red light, the maximum photoluminescence peak wavelength of the quantum dot may be greater than or equal to about 600 nm, greater than or equal to about 610 nm, greater than or equal to about 611 nm, greater than or equal to about 612 nm, greater than or equal to about 613 nm, greater than or equal to about 614 nm, greater than or equal to about 615 nm, greater than or equal to about 616 nm, greater than or equal to about 617 nm, greater than or equal to about 618 nm, greater than or equal to about 619 nm, or greater than or equal to about 620 nm. The maximum photoluminescence peak wavelength of the quantum dot may be less than or equal to about 650 nm, less than or equal to about 640 nm, less than or equal to about 635 nm, less than or equal to about 634 nm, less than or equal to about 633 nm, less than or equal to about 632 nm, less than or equal to about 631 nm, or less than or equal to about 630 nm.

[0127] In the UV-Vis absorption spectrum of the quantum dots, the first absorption peak wavelength may exist in a range greater than about 450 nm, greater than or equal to about 500 nm, greater than or equal to about 550 nm, or greater than or equal to about 570 nm and less than the maximum photoluminescence peak wavelength (for example, less than or equal to about 620 nm, less than or equal to about 610 nm, less than or equal to about 600 nm, or less than or equal to about 590 nm).

[0128] In one embodiment, the quantum dot may emit green light and the first absorption peak wavelength may be greater than or equal to about 480 nm, greater than or equal to about 485 nm, greater than or equal to about 490 nm, greater than or equal to about 500 nm, greater than or equal to about 510 nm, or greater than or equal to about 515 nm. In one embodiment, the quantum dot may emit green light and the first absorption peak wavelength may be less than or equal to about 540 nm, less than or equal to about 530 nm, less than or equal to about 529 nm, less than or equal to about 528 nm, less than or equal to about 527 nm, less than or equal to about 526 nm, less than or equal to about 525 nm, less than or equal to about 524 nm, less than or equal to about 523 nm, less than or equal to about 522 nm, less than or equal to about 521 nm, or less than or equal to about 520 nm.

[0129] In one embodiment, the quantum dots may emit red light and the first absorption peak wavelength may be greater than or equal to about 595 nm, greater than or equal to about 596 nm, greater than or equal to about 597 nm, greater than or equal to about 598 nm, greater than or equal to about 599 nm, greater than or equal to about 600 nm, greater than or equal to about 601 nm, greater than or equal to about 602 nm, greater than or equal to about 603 nm, greater than or equal to about 604 nm, greater than or equal to about 605 nm, greater than or equal to about 606 nm, greater than or equal to about 607 nm, greater than or equal to about 608 nm, greater than or equal to about 609 nm, greater than or equal to about 610 nm, greater than or equal to about 611 nm, or greater than or equal to about 612 nm.

[0130] In one embodiment, the quantum dots may emit red light and the first absorption peak wavelength may be less than or equal to about 625 nm, less than or equal to about 624 nm, less than or equal to about 623 nm, less than or equal to about 622 nm, less than or equal to about 621 nm, less than or equal to about 620 nm, or less than or equal to about 619 nm.

[0131] The difference between the wavelength of the maximum photoluminescence peak and the first absorption peak wavelength (hereinafter, also referred to as Stokes shift) may be less than or equal to about 20 nm, less than or equal to about 19 nm, less than or equal to about 18 nm, less than or equal to about 17 nm, or less than or equal to about 16 nm.

[0132] In quantum dots, Stokes shift refers to the difference between photoluminescence energy and absorption energy. Therefore, the Stokes shift can be represented by the difference between the maximum photoluminescence peak wavelength (energy) in the photoluminescence spectrum and the first absorption peak wavelength (nm) (or energy, microelectron volts (meV)) in the UV-Vis absorption spectrum. As used herein, "first absorption peak (or first excitation absorption peak)" refers to the main peak that first appears from the lower energy region in the UV-Vis absorption spectrum. Without wishing to be bound by any theory, it is believed that the Stokes shift may depend on the size, composition, or a combination thereof of the quantum dot particles. Without wishing to be bound by any theory, it is also believed that the surface state of the quantum dots may also have an effect on the Stokes shift. Therefore, the Stokes shift of the quantum dots may represent the size, composition, surface state (e.g., the presence of surface defects), or a combination thereof of the quantum dots. The inventors have also found that the Stokes shift of core-shell quantum dots may have an effect on the electroluminescent properties and stability (e.g., T 50 lifespan) has a direct impact.

[0133] The quantum dots may have an average particle size of about 8 nm or more, about 9 nm or more, or about 10 nm or more. The average particle size of the quantum dots may be about 50 nm or less, about 45 nm or less, about 40 nm or less, about 39 nm or less, about 38 nm or less, about 37 nm or less, about 36 nm or less, about 35 nm or less, about 34 nm or less, about 33 nm or less, about 32 nm or less, about 31 nm or less, about 30 nm or less, about 29 nm or less, about 36 nm or less. The particle size of the quantum dot may be the diameter of the particle. When the particle is non-spherical, the size of the quantum dot may be the diameter of a circle converted from the area of ​​a two-dimensional image obtained by electron microscopy analysis (e.g., an equivalent diameter).

[0134] The standard deviation of the particle size distribution of the quantum dots may be less than or equal to about 20%, less than or equal to about 19%, less than or equal to about 18%, less than or equal to about 17%, less than or equal to about 16%, or less than or equal to about 15% of its average size. In one embodiment, the standard deviation of the particle size distribution of the quantum dots may be less than or equal to about 14%, less than or equal to about 13%, less than or equal to about 12%, less than or equal to about 11%, or less than or equal to about 10% of its average size. The standard deviation of the particle size distribution of the quantum dots may be greater than or equal to about 5%, greater than or equal to about 6%, greater than or equal to about 7%, greater than or equal to about 8%, greater than or equal to about 9%, greater than or equal to about 10%, or greater than or equal to about 11% of its average size.

[0135] The quantum dots may have a quantum yield of greater than or equal to about 60%, greater than or equal to about 65%, greater than or equal to about 70%, greater than or equal to about 75%, or greater than or equal to about 80%.

[0136] In one embodiment, the semiconductor nanocrystal core may include indium phosphide. The semiconductor nanocrystal core may further include zinc. The semiconductor nanocrystal core may not include zinc. The size of the core may be appropriately selected. In one embodiment, the size of the core may be greater than or equal to about 1 nm, greater than or equal to about 1.5 nm, greater than or equal to about 2 nm, or greater than or equal to about 2.5 nm. In one embodiment, the size of the core may be less than or equal to about 5 nm, less than or equal to about 4 nm, less than or equal to about 4.5 nm, less than or equal to about 3.5 nm, or less than or equal to about 3 nm.

[0137] The first semiconductor nanocrystal shell may include zinc selenide (e.g., ZnSe). The first semiconductor nanocrystal shell may not include sulfur (S). In one embodiment, the first semiconductor nanocrystal shell may not include ZnSeS. The first semiconductor nanocrystal shell may be directly disposed on the semiconductor nanocrystal core. The first semiconductor nanocrystal shell may have a thickness greater than about 4 monolayers (ML), such as greater than about 4.5 ML, greater than or equal to about 5 ML, greater than or equal to about 6 ML, greater than or equal to about 7 ML, or greater than or equal to about 8 ML. In one embodiment, the thickness of the first semiconductor nanocrystal shell may be greater than or equal to about 9 ML, or greater than or equal to about 10 ML. The thickness of the first semiconductor nanocrystal shell may be less than about 5nm. The thickness of the first semiconductor nanocrystal shell may be less than or equal to about 15 ML, less than or equal to about 14 ML, or less than or equal to about 13 ML.

[0138] The second semiconductor nanocrystal shell may include zinc sulfide (e.g., ZnS). The second semiconductor nanocrystal shell may not include selenium. The second semiconductor nanocrystal shell may be directly disposed on the first semiconductor nanocrystal shell. The thickness of the second semiconductor nanocrystal shell may be appropriately selected. The second semiconductor nanocrystal shell may be the outermost layer of the quantum dot. In one embodiment, the quantum dot may have a core-multi-shell structure, wherein the quantum dot includes a core comprising indium phosphide (e.g., InP or InZnP), a first shell directly disposed on the core and including ZnSe, and a second shell directly disposed on the first shell and including ZnS.

[0139] In one embodiment, the quantum dot may include an InP core (eg, may emit red light) and the amount of indium relative to the chalcogen may be within a predetermined range.

[0140] In one embodiment of the quantum dot, the molar ratio of indium to the sum of sulfur and selenium (i.e., [In:(Se+S)], which may be described as the value of [In / (Se+S)] hereinafter) may be less than 0.1:1, less than or equal to about 0.09:1, less than or equal to about 0.08:1, less than or equal to about 0.07:1, less than or equal to about 0.06:1, or less than or equal to about 0.05:1. The molar ratio of indium to the sum of sulfur and selenium may be greater than or equal to about 0.02:1, greater than or equal to about 0.03:1, or greater than or equal to about 0.04:1.

[0141] In one embodiment of the quantum dots, the molar ratio of sulfur to selenium (S / Se) may be less than 4.5:1, for example, less than or equal to about 4:1, less than or equal to about 3.5:1, less than or equal to about 3:1, less than or equal to about 2.5:1, less than or equal to about 2:1, less than or equal to about 1.5:1, or less than or equal to about 1:1. In one embodiment of the quantum dots, the molar ratio of sulfur to selenium (S / Se) may be greater than or equal to about 0.01:1, greater than or equal to about 0.05:1, greater than or equal to about 0.09:1, greater than or equal to about 0.1:1, greater than or equal to about 0.11:1, greater than or equal to about 0.12:1, greater than or equal to about 0.13:1, greater than or equal to about 0.14:1, greater than or equal to about 0.15:1, greater than or equal to about 0.16:1, greater than or equal to about 0.17:1, greater than or equal to about 0.18:1, greater than or equal to about 0.19:1, greater than or equal to about 0.20:1, greater than or equal to about 0.3:1, greater than or equal to about 0.4:1, greater than or equal to about 0.5:1, greater than or equal to about 0.6:1, greater than or equal to about 0.7:1, greater than or equal to about 0.8:1, or greater than or equal to about 0.9:1.

[0142] In the quantum dots, the molar ratio of zinc to indium may be greater than or equal to about 15:1, greater than or equal to about 16:1, greater than or equal to about 17:1, greater than or equal to about 18:1, greater than or equal to about 19:1, greater than or equal to about 20:1, greater than or equal to about 21:1, or greater than or equal to about 22:1.

[0143] In the quantum dots, a molar ratio of zinc to indium may be less than about 52:1, less than or equal to about 51:1, less than or equal to about 50:1, less than or equal to about 49:1, less than or equal to about 48:1, or less than or equal to about 47:1.

[0144] The shape of the quantum dots is not particularly limited, and may be, for example, spherical, polyhedral, pyramidal, multi-legged, or cubical, nanotubes, nanowires, nanofibers, nanosheets, or a combination thereof, but is not limited thereto.

[0145] The quantum dot may include an organic ligand, an organic solvent, or a combination thereof, which will be described below, on a surface of the quantum dot. The organic ligand, the organic solvent, or the combination thereof may be bound to a surface of the quantum dot.

[0146] In one embodiment, a method of making the above-mentioned quantum dots includes: providing the above-mentioned semiconductor nanocrystal core; and forming a shell on the core.

[0147] The formation of the shell may include:

[0148] heating a first mixture comprising a first shell precursor comprising zinc, an organic ligand, and an organic solvent;

[0149] adding semiconductor nanocrystal cores (e.g., not in a heated state) comprising indium and phosphorus to the heated first mixture,

[0150] heating the first mixture to a first reaction temperature and adding a precursor containing selenium to the first mixture to react for a predetermined time,

[0151] The temperature of the resulting mixture is increased to a second reaction temperature and a precursor containing selenium and a precursor containing sulfur are separately added to react.

[0152] The method may further include adding the first shell precursor to the resulting mixture.

[0153] The amounts of the selenium-containing precursor and the sulfur-containing precursor relative to the core (and optionally, the amounts of the precursors added, the temperature at which the precursors are added, the reaction temperature and time, or a combination thereof) can be controlled to obtain the desired composition and size of the quantum dots (e.g., within the above ranges) as well as their properties (e.g., Stokes shift).

[0154] The details of the quantum dots are the same as described above.

[0155] The first shell precursor is not particularly limited and can be appropriately selected. In one embodiment, the first shell precursor may include Zn metal powder, alkylated Zn compound, alcohol Zn, carboxylic acid Zn, Zn nitrate, Zn perchlorate, Zn sulfate, Zn acetylacetonate, Zn halide, zinc carbonate, Zn cyanide, Zn hydroxide, Zn oxide, Zn peroxide, or a combination thereof. Examples of the first shell precursor may include dimethyl zinc, diethyl zinc, zinc acetate, zinc acetylacetonate, zinc iodide, zinc bromide, zinc chloride, zinc fluoride, zinc carbonate, zinc cyanide, zinc nitrate, zinc oxide, zinc peroxide, zinc perchlorate, zinc sulfate, and the like. One shell precursor or a plurality of different first shell precursors may be used.

[0156] In one embodiment, the organic ligand may include RCOOH, RNH 2 , R2 NH, R 3 N, RSH, RH 2 PO, R 2 HPO, R 3 PO, RH 2 P.R 2 HP, R 3 P, ROH, RCOOR', RPO(OH) 2 , RHPOOH, R 2 POOH (wherein R and R' are the same or different and are each independently a C1-C40 (e.g., C3-C24) aliphatic hydrocarbon group such as an alkyl, alkenyl, or alkynyl group or a C6-C20 aromatic hydrocarbon group such as an aryl group such as a phenyl group), a polymeric organic ligand, or a combination thereof.

[0157] The organic ligands may coordinate, for example, bind to the surface of the obtained nanocrystals and may allow the nanocrystals to be well dispersed in solution, have an effect on the luminescent and electrical properties of the quantum dots, or a combination thereof.

[0158] Examples of the organic ligand compound may include:

[0159] Thiol compounds such as methyl mercaptan, ethyl mercaptan, propyl mercaptan, butyl mercaptan, pentyl mercaptan, hexyl mercaptan, octyl mercaptan, dodecanethiol, hexadecanethiol, octadecanethiol, benzyl mercaptan, or combinations thereof;

[0160] Amine compounds such as methylamine, ethylamine, propylamine, butylamine, pentylamine, hexylamine, octylamine, nonylamine, decylamine, dodecylamine, hexadecylamine, octadecylamine, dimethylamine, diethylamine, dipropylamine, tributylamine, trioctylamine, or combinations thereof;

[0161] Carboxylic acid compounds such as formic acid, acetic acid, propionic acid, butyric acid, valeric acid, hexanoic acid, heptanoic acid, octanoic acid, dodecanoic acid, hexadecanoic acid, octadecanoic acid, oleic acid, benzoic acid, or combinations thereof;

[0162] Phosphine compounds such as methyl phosphine, ethyl phosphine, propyl phosphine, butyl phosphine, pentyl phosphine, octyl phosphine, dioctyl phosphine, tributyl phosphine, trioctyl phosphine, or combinations thereof;

[0163] Phosphine oxide compounds such as methylphosphine oxide, ethylphosphine oxide, propylphosphine oxide, butylphosphine oxide, pentylphosphine oxide, tributylphosphine oxide, octylphosphine oxide, dioctylphosphine oxide, trioctylphosphine oxide, or combinations thereof;

[0164] Diphenylphosphine, triphenylphosphine, or oxide compounds thereof, or combinations thereof;

[0165] Mono- or di-(C5-C20 alkyl)phosphinic acid such as mono- or di-hexylphosphinic acid, mono- or di-octylphosphinic acid, mono- or didodecylphosphinic acid, mono- or didetradecylphosphinic acid, mono- or didhexadecylphosphinic acid, mono- or didoctadecylphosphinic acid, or a combination thereof;

[0166] C5-C20 alkylphosphonic acid such as hexylphosphonic acid, octylphosphonic acid, dodecylphosphonic acid, tetradecylphosphonic acid, hexadecylphosphonic acid, octadecylphosphonic acid, or a combination thereof;

[0167] or a combination thereof.

[0168] One or more organic ligands may be used.

[0169] Examples of the organic solvent may include C6-C22 primary amines such as hexadecylamine, C6-C22 secondary amines such as dioctylamine, C6-C40 tertiary amines such as trioctylamine, nitrogen-containing heterocyclic compounds such as pyridine, C6-C40 olefins such as octadecene, C6-C40 aliphatic hydrocarbons such as hexadecane, octadecane, squalene, or squalane, aromatic hydrocarbons substituted with C6-C30 alkyl groups such as phenyldodecane, phenyltetradecane, or phenylhexadecane, a primary, secondary, or tertiary phosphine containing at least one (e.g., 1, 2, or 3) C6-C22 alkyl group (e.g., trioctylphosphine), a phosphine oxide containing at least one (e.g., 1, 2, or 3) C6-C22 alkyl group (e.g., trioctylphosphine oxide), a C12-C22 aromatic ether such as phenyl ether or benzyl ether, or a combination thereof.

[0170] The solvent used and the amount of solvent used can be selected taking into account the precursor and organic ligand used.

[0171] The first mixture can be heated to a temperature of greater than or equal to about 100°C, greater than or equal to about 120°C, greater than or equal to about 150°C, greater than or equal to about 200°C, greater than or equal to about 250°C, or greater than or equal to about 270°C, for a predetermined time (e.g., greater than or equal to about 5 minutes and less than or equal to about 1 hour (h)), for example, under vacuum, an inert atmosphere, or a combination thereof.

[0172] The details of the semiconductor nanocrystal core including indium and phosphorus are the same as those set forth above. The core may be commercially available or may be synthesized by a suitable method. The method for preparing the core is not particularly limited and a suitable method for manufacturing a core based on indium phosphide may be used. In one embodiment, the core may be formed by hot injection, wherein a solution including a metal precursor (e.g., an indium precursor) and an optional ligand is heated to a high temperature (e.g., greater than or equal to about 200° C.) and a phosphorus precursor is injected into the hot solution.

[0173] The precursor containing selenium is not particularly limited and can be appropriately selected. For example, the precursor containing selenium can include selenium-trioctylphosphine (Se-TOP), selenium-tributylphosphine (Se-TBP), selenium-triphenylphosphine (Se-TPP), or a combination thereof, but is not limited thereto.

[0174] The first reaction temperature may be greater than or equal to about 280°C, greater than or equal to about 290°C, greater than or equal to about 300°C, greater than or equal to about 310°C, or greater than or equal to about 315°C and less than or equal to about 350°C, less than or equal to about 340°C, or less than or equal to about 330°C.

[0175] After or during heating the second mixture to the first reaction temperature, a precursor including selenium may be injected at least once (eg, at least twice or at least three times).

[0176] The reaction mixture can be maintained at the first reaction temperature for a predetermined time (e.g., 10 minutes to 60 minutes, 15 minutes to 55 minutes, or 20 minutes to 50 minutes). Thus, a first semiconductor nanocrystal shell comprising zinc and selenium can be formed to obtain a mixture of particles comprising the above shell on the core.

[0177] Then, the temperature of the mixture can be raised to a second reaction temperature, during which time or when the mixture reaches the second reaction temperature, a precursor comprising selenium can be added again. The second reaction temperature can be greater than the first reaction temperature. In one embodiment, the second reaction temperature can be at least about 10°C, at least about 20°C, or at least about 30°C greater than the first reaction temperature. The second reaction temperature can be controlled within the range of about 270°C to about 350°C, about 275°C to about 345°C, about 280°C to about 340°C, about 285°C to about 335°C, about 290°C to about 330°C, or about 295°C to about 325°C.

[0178] The first reaction temperature, the second reaction temperature, and the time at each reaction temperature may be selected in consideration of the desired thickness of the shell comprising the first semiconductor nanocrystal, the desired thickness of the shell comprising the second semiconductor nanocrystal, the precursor, etc. In one embodiment, the first and second temperatures, the duration at each reaction temperature, and the amount of the precursor may be controlled so that the first semiconductor nanocrystal shell may have a thickness within the above range.

[0179] In this reaction system, the amount of selenium as added per 1 mole of indium may be greater than or equal to about 10 moles, greater than or equal to about 15 moles, greater than or equal to about 20 moles, greater than or equal to about 25 moles, greater than or equal to about 30 moles, greater than or equal to about 35 moles, greater than or equal to about 40 moles, or greater than or equal to about 45 moles and less than or equal to about 50 moles, less than or equal to about 45 moles, less than or equal to about 40 moles, less than or equal to about 35 moles, less than or equal to about 30 moles, less than or equal to about 25 moles, or less than or equal to about 20 moles, but not limited thereto. The amount of selenium may be selected in consideration of reaction temperature / time, the desired thickness of the first semiconductor nanocrystal shell, the precursor comprising selenium, or a combination thereof.

[0180] The injection of the sulfur precursor may begin after (eg, the entire amount of) the added selenium-containing precursor is used up (consumed) in the reaction mixture.

[0181] In an embodiment, the method may not include reducing the temperature of the reaction mixture (eg, to or below 100°C, to or below 50°C, or to or below 30°C, or to room temperature).

[0182] The sulfur-containing precursor is not particularly limited and can be appropriately selected. The sulfur-containing precursor can include hexyl mercaptan, octyl mercaptan, decanethiol, dodecanethiol, hexadecanethiol, mercaptopropylsilane, sulfur-trioctylphosphine (S-TOP), sulfur-tributylphosphine (S-TBP), sulfur-triphenylphosphine (S-TPP), sulfur-trioctylamine (S-TOA), trimethylsilyl sulfide, ammonium sulfide, sodium sulfide, or a combination thereof. The sulfur-containing precursor can be injected at least once (e.g., at least twice).

[0183] In this reaction system, the amount of the precursor containing sulfur relative to the indium of the core may be selected in consideration of the desired composition of the resulting quantum dots, the reactivity of the precursor containing sulfur, and the second reaction temperature.

[0184] In one embodiment, the amount of sulfur added per 1 mole of indium may be greater than or equal to about 1 mole, greater than or equal to about 3 moles, greater than or equal to about 5 moles, greater than or equal to about 7 moles, greater than or equal to about 9 moles, greater than or equal to about 11 moles, greater than or equal to about 13 moles, or greater than or equal to about 15 moles and less than or equal to about 30 moles, less than or equal to about 25 moles, less than or equal to about 20 moles, less than or equal to about 19 moles, less than or equal to about 18 moles, less than or equal to about 17 moles, less than or equal to about 16 moles, less than or equal to about 15 moles, or less than or equal to about 14 moles, but is not limited thereto.

[0185] When a non-solvent is added to the obtained reaction solution, the quantum dots coordinated by the organic ligand can be separated (for example, precipitated). The non-solvent can be a polar solvent miscible with the solvent used in the reaction and in which the nanocrystal cannot be dispersed. The non-solvent can be selected depending on the solvent used in the reaction and can be, for example, acetone, ethanol, butanol, isopropanol, ethylene glycol, water, tetrahydrofuran (THF), dimethyl sulfoxide (DMSO), diethyl ether, formaldehyde, acetaldehyde, but is not limited thereto. The separation can be carried out by centrifugation, precipitation, chromatography, or distillation. If desired, the separated nanocrystals can be added to a washing solvent and washed. The washing solvent is not particularly limited and can include a solvent with a solubility parameter similar to the solubility parameter of the ligand and can, for example, include hexane, heptane, octane, chloroform, toluene, benzene, etc.

[0186] In one embodiment, the emission layer 13 may have a thickness of greater than or equal to about 5 nm, greater than or equal to about 6 nm, greater than or equal to about 7 nm, greater than or equal to about 8 nm, greater than or equal to about 9 nm, greater than or equal to about 10 nm, greater than or equal to about 11 nm, greater than or equal to about 12 nm, greater than or equal to about 13 nm, greater than or equal to about 14 nm, greater than or equal to about 15 nm, greater than or equal to about 16 nm, greater than or equal to about 17 nm, greater than or equal to about 18 nm, greater than or equal to about 19 nm, or greater than or equal to about 20 nm. The thickness of the emission layer 13 may be less than or equal to about 200 nm, less than or equal to about 190 nm, less than or equal to about 180 nm, less than or equal to about 170 nm, less than or equal to about 160 nm, less than or equal to about 150 nm, less than or equal to about 140 nm, less than or equal to about 130 nm, less than or equal to about 120 nm, less than or equal to about 110 nm, less than or equal to about 100 nm, less than or equal to about 90 nm, less than or equal to about 80 nm, less than or equal to about 70 nm, less than or equal to about 60 nm, less than or equal to about 50 nm, less than or equal to about 40 nm, less than or equal to about 30 nm, or less than or equal to about 20 nm.

[0187] In one embodiment, the emission layer 13 may have a HOMO energy level of about 5.4 eV or more, about 5.5 eV or more, about 5.6 eV or more, about 5.7 eV or more, about 5.8 eV or more, about 5.9 eV or more, or about 6.0 eV or more. The HOMO energy level of the emission layer 13 may be about 7.0 eV or less, about 6.8 eV or less, about 6.7 eV or less, about 6.5 eV or less, about 6.3 eV or less, or about 6.2 eV or less. The HOMO energy level of the emission layer 13 may be about 5.4 eV to about 5.9 eV.

[0188] In one embodiment, the emission layer 13 may have a LUMO energy level of less than or equal to about 3.9 eV, less than or equal to about 3.8 eV, less than or equal to about 3.7 eV, less than or equal to about 3.6 eV, less than or equal to about 3.5 eV, less than or equal to about 3.4 eV, less than or equal to about 3.3 eV, less than or equal to about 3.2 eV, or less than or equal to about 3.0 eV. The LUMO energy level of the emission layer 13 may be greater than or equal to about 2.5 eV, greater than or equal to about 2.6 eV, greater than or equal to about 2.7 eV, or greater than or equal to about 2.8 eV. In one embodiment, the emission layer 13 may have an energy band gap of about 2.4 eV to about 3.5 eV.

[0189] In one embodiment, the hole auxiliary layer 12 may be disposed between the first electrode 11 (e.g., anode) and the emission layer 13. The hole auxiliary layer 12 may have one layer or two or more layers, and may include, for example, a hole injection layer (HIL), a hole transport layer (HTL), an electron blocking layer, or a combination thereof.

[0190] The hole assisting layer 12 may have a HOMO energy level that may match the HOMO energy level of the emission layer 13 and may enhance, for example, assist migration of holes from the hole assisting layer 12 into the emission layer 13 .

[0191] The HOMO energy level of the hole-assisting layer 12 (e.g., a hole transport layer (HTL)) contacting the emission layer may be the same as the HOMO energy level of the emission layer 13 or a value less than the HOMO energy level of the emission layer 13 in the range of less than or equal to about 1.0 eV, for example, about 0.01 eV-about 0.8 eV, about 0.01 eV-about 0.7 eV, about 0.01 eV-about 0.5 eV, about 0.01 eV-about 0.4 eV, about 0.01 eV-about 0.3 eV, about 0.01 eV-about 0.2 eV, or about 0.01 eV-about 0.1 eV.

[0192] The HOMO energy level of the hole assisting layer 12 may be greater than or equal to about 5.0 eV, greater than or equal to about 5.2 eV, greater than or equal to about 5.4 eV, greater than or equal to about 5.6 eV, or greater than or equal to about 5.8 eV. In one embodiment, the HOMO energy level of the hole assisting layer 12 may be about 5.0 eV to about 7.0 eV, about 5.2 eV to about 6.8 eV, about 5.4 eV to about 6.8 eV, about 5.4 eV to about 6.7 eV, about 5.4 eV to about 6.5 eV, about 5.4 eV to about 6.3 eV, about 5.4 eV to about 6.2 eV, about 5.4 eV to about 6.1 eV, about 5.6 eV to about 7.0 eV, about 5.6 eV to about 6.8 eV, about 5 .6eV to about 6.7eV, about 5.6eV to about 6.5eV, about 5.6eV to about 6.3eV, about 5.6eV to about 6.2eV, about 5.6eV to about 6.1eV, about 5.8eV to about 7.0eV, about 5.8eV to about 6.8eV, about 5.8eV to about 6.7eV, about 5.8eV to about 6.5eV, about 5.8eV to about 6.3eV, about 5.8eV to about 6.2eV, or about 5.8eV to about 6.1eV.

[0193] In one embodiment, the hole auxiliary layer 12 may include a hole injection layer closer to the first electrode 11 and a hole transport layer closer to the emission layer 13. In one embodiment, the HOMO energy level of the hole injection layer may be about 5.0 eV to about 6.0 eV, about 5.0 eV to about 5.5 eV, or about 5.0 eV to about 5.4 eV. In one embodiment, the HOMO energy level of the hole transport layer may be about 5.2 eV to about 7.0 eV, about 5.4 eV to about 6.8 eV, about 5.4 eV to about 6.7 eV, about 5.4 eV to about 6.5 eV, about 5.4 eV to about 6.3 eV, about 5.4 eV to about 6.2 eV, or about 5.4 eV to about 6.1 eV.

[0194] The material included in the hole auxiliary layer 12 (e.g., a hole transport layer or a hole injection layer) is not particularly limited and may include, for example, poly(9,9-dioctyl-fluorene-2,7-diyl-co-N-(4-butylphenyl)-diphenylamine) (TFB), polyarylamine (polyarylamine), poly(N-vinylcarbazole), poly(3,4-ethylenedioxythiophene) (PEDOT), poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS), polyaniline, polypyrrole, N,N, N',N'-tetrakis(4-methoxyphenyl)-benzidine (TPD), 4,4'-bis[N-(1-naphthyl)-N-phenyl-amino]biphenyl (α-NPD), m-MTDATA (4,4',4"-tri[phenyl(m-tolyl)amino]triphenylamine), 4,4',4"-tri(N-carbazolyl)-triphenylamine (TCTA), 1,1-bis[(di-4-tolylamino)phenyl]cyclohexane (TAPC), p-type metal oxides (e.g., NiO, WO 3 、MoO 3 etc.), carbon-based materials such as graphene oxide, or a combination thereof, but are not limited thereto.

[0195] The electron blocking layer (EBL) may include, for example, poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS), poly(9,9-dioctyl-fluorene-2,7-diyl-co-N-(4-butylphenyl)-diphenylamine) (TFB), polyarylamine, poly(N-vinylcarbazole), polyaniline, polypyrrole, N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine (TPD), 4,4'-bis[N-(1-naphthyl)-N-phenyl-amino]biphenyl (α-NPD), m-MTDATA, 4,4',4"-tris(N-carbazolyl)-triphenylamine (TCTA), or a combination thereof, but is not limited thereto.

[0196] In the hole auxiliary layer, the thickness of each layer can be appropriately selected, for example, depending on the desired characteristics of each layer. For example, the thickness of each layer can be greater than or equal to about 10nm, such as greater than or equal to about 15nm, greater than or equal to about 20nm and less than or equal to about 100nm, such as less than or equal to about 90nm, less than or equal to about 80nm, less than or equal to about 70nm, less than or equal to about 60nm, less than or equal to about 50nm, less than or equal to about 40nm, less than or equal to about 35nm, or less than or equal to about 30nm, but is not limited thereto.

[0197] The electron assisting layer 14 is disposed between the emission layer 13 and the second electrode 15. The electron assisting layer 14 may include, for example, an electron injection layer (EIL) facilitating injection of electrons, an electron transport layer (ETL) facilitating transport of electrons, a hole blocking layer (HBL) blocking movement of holes, or a combination thereof, but is not limited thereto.

[0198] In one embodiment, the EIL may be disposed between the ETL and the cathode. In one embodiment, the HBL may be disposed between the ETL (or the EIL) and the emission layer, but is not limited thereto. In one embodiment, the thickness of each layer may be greater than or equal to about 1 nm and less than or equal to about 500 nm, but is not limited thereto. The EIL may be an organic layer (e.g., prepared by vapor deposition). The ETL may include inorganic oxide nanoparticles, an organic layer (e.g., prepared by vapor deposition), or a combination thereof.

[0199] The electron transport layer, the electron injection layer, or a combination thereof may include, for example, 1,4,5,8-naphthalene-tetracarboxylic dianhydride (NTCDA), bathocuproine (BCP), tris[3-(3-pyridyl)- yl]borane (3TPYMB), LiF, Alq 3 , Gaq 3 、Inq 3 、Znq 2 、Zn(BTZ) 2 、BeBq 2 , ET204 (8-(4-(4,6-di(naphthalene-2-yl)-1,3,5-triazine-2-yl)phenyl)quinolone), 8-hydroxyquinoline lithium (Liq), n-type metal oxides (e.g., ZnO, HfO 2 etc.), or a combination thereof, but not limited thereto.

[0200] The hole blocking layer (HBL) may include, for example, 1,4,5,8-naphthalene-tetracarboxylic dianhydride (NTCDA), bathocuproin (BCP), tris[3-(3-pyridyl)- yl]borane (3TPYMB), LiF, Alq 3 , Gaq 3 、Inq 3 、Znq 2 、Zn(BTZ) 2 、BeBq 2 , or a combination thereof, but is not limited thereto.

[0201] In one embodiment, the electron assist layer 14 (e.g., the electron transport layer) may include a plurality of nanoparticles. The nanoparticles include a metal oxide including zinc (e.g., zinc metal oxide). In the device of the embodiment, the quantum dots having the above characteristics (e.g., composition, size, Stokes shift, etc.) may achieve desirable electroluminescent properties (e.g., high levels of EQE and improved brightness) when combined with an electron assist layer based on, for example, zinc metal oxide. In addition, when combined with an electron assist layer based on, for example, zinc metal oxide, the device including the above quantum dots may exhibit improved stability (e.g., improved T 50 ).

[0202] The metal oxide may include zinc oxide, zinc magnesium oxide, or a combination thereof. The metal oxide (eg, zinc metal oxide) may include Zn 1-x M x O (wherein M is Mg, Ca, Zr, W, Li, Ti, Y, Al, or a combination thereof, and 0≤x≤0.5). In one embodiment, M may be magnesium (Mg). In one embodiment, x may be zero. In one embodiment, x may be greater than or equal to about 0.01, greater than or equal to about 0.02, greater than or equal to about 0.03, greater than or equal to about 0.04, greater than or equal to about 0.05, greater than or equal to about 0.06, greater than or equal to about 0.07, greater than or equal to about 0.08, greater than or equal to about 0.09, or greater than or equal to about 0.1 and less than or equal to about 0.45, less than or equal to about 0.4, less than or equal to about 0.35, less than or equal to about 0.3, less than or equal to about 0.25, less than or equal to about 0.2, or less than or equal to about 0.15.

[0203] An absolute value of a LUMO energy level of the quantum dots included in the emission layer may be smaller than an absolute value of a LUMO energy level of the metal oxide. In one embodiment, an absolute value of a LUMO energy level of the quantum dots may be greater than an absolute value of a LUMO energy level of the metal oxide.

[0204] The average size of the nanoparticles may be greater than or equal to about 1 nm, such as greater than or equal to about 1.5 nm, greater than or equal to about 2 nm, greater than or equal to about 2.5 nm, or greater than or equal to about 3 nm and less than or equal to about 10 nm, less than or equal to about 9 nm, less than or equal to about 8 nm, less than or equal to about 7 nm, less than or equal to about 6 nm, or less than or equal to about 5 nm. The nanoparticles may not have a rod shape. The nanoparticles may not have a nanowire shape.

[0205] In one embodiment, the thickness of the electron assisting layer 14 (e.g., the thickness of each of the electron injection layer, the electron transport layer, or the hole blocking layer) may be greater than or equal to about 5 nm, greater than or equal to about 6 nm, greater than or equal to about 7 nm, greater than or equal to about 8 nm, greater than or equal to about 9 nm, greater than or equal to about 10 nm, greater than or equal to about 11 nm, greater than or equal to about 12 nm, greater than or equal to about 13 nm, greater than or equal to about 14 nm, greater than or equal to about 15 nm, greater than or equal to about 16 nm, greater than or equal to about 17 nm, greater than or equal to about 18 nm, greater than or equal to about 19 nm, greater than or equal to about 20 nm, greater than or equal to about 21 nm, greater than or equal to about 22 nm, greater than or equal to about 23 nm, greater than or equal to about 24 nm, greater than or equal to about 25 nm, greater than or equal to about 26 nm, greater than or equal to about 27 nm, greater than or equal to about 28 nm, greater than or equal to about 29 nm, greater than or equal to about 30 nm, greater than or equal to about 31 nm, greater than or equal to about 32 nm, greater than or equal to about 33 nm, greater than or equal to about 34 nm, greater than or equal to about 35 nm, greater than or equal to about 36 nm, greater than or equal to about 37 nm, greater than or equal to about 38 nm, greater than or equal to about 39 nm, greater than or equal to about 40 nm, greater than or equal to about 41 nm, greater than or equal to about 42 nm, greater than or equal to about 43 nm, greater than or equal to about 44 nm, greater than or equal to about 45 nm, greater than or equal to about 46 nm, greater than or equal to about 47 nm or equal to about 17 nm, greater than or equal to about 18 nm, greater than or equal to about 19 nm, or greater than or equal to about 20 nm and less than or equal to about 120 nm, less than or equal to about 110 nm, less than or equal to about 100 nm, less than or equal to about 90 nm, less than or equal to about 80 nm, less than or equal to about 70 nm, less than or equal to about 60 nm, less than or equal to about 50 nm, less than or equal to about 40 nm, less than or equal to about 30 nm, or less than or equal to about 25 nm, but is not limited thereto.

[0206] The device according to one embodiment has a positive (normal) structure. In the device according to the embodiment, the anode 11a disposed on the transparent substrate 100 may include a metal oxide-based transparent electrode (e.g., an ITO electrode) and the cathode 15a facing the anode may include a metal with a relatively low work function (Mg, Al, etc.). For example, a hole auxiliary layer 20, for example, a hole transport layer including TFB, poly (9-vinyl carbazole) (PVK), or a combination thereof; a hole injection layer including PEDOT:PSS, a p-type metal oxide, or a combination thereof; or a combination thereof may be disposed between the anode 11a, such as a transparent anode and the emission layer 30. The electron auxiliary layer 40, such as an electron injection layer / transport layer, may be disposed between the quantum dot emission layer 30 and the cathode 15a. (See Figure 2 )

[0207] The device according to one embodiment has an inverted structure. Here, the cathode 15a disposed on the transparent substrate 100 may include a metal oxide-based transparent electrode (e.g., ITO) and the anode 11a facing the cathode may include a relatively high work function metal (e.g., Au, Ag, etc.). For example, an n-type metal oxide (ZnO) may be disposed between the cathode 15a, such as a transparent cathode, and the emission layer 30 as an electron auxiliary layer 40 (e.g., an electron transport layer (ETL)). MoO as the hole auxiliary layer 20 3 or another p-type metal oxide (e.g., a hole transport layer (HTL) including TFB, PVK, or a combination thereof; a hole transport layer (HTL) including MoO 3or another p-type metal oxide hole injection layer (HIL); or a combination thereof) may be disposed between the metal anode 11a and the quantum dot emission layer 30 as a hole auxiliary layer (eg, a hole transport layer (HTL)). (See Figure 3 )

[0208] One embodiment relates to a method of making the above-mentioned electroluminescent device.

[0209] The method includes: forming an emission layer including the quantum dots (e.g., the pattern of the quantum dots described above) on a first electrode; optionally forming a charge assist layer on the emission layer; and forming a second electrode on the emission layer (or the optional charge assist layer). The charge assist layer may be an electron assist layer. The method may further include forming a charge assist layer (e.g., a hole assist layer) on the first electrode before forming the emission layer. In this case, the emission layer may be formed on the charge assist layer disposed on the first electrode.

[0210] The details of the first electrode, the emission layer, the charge assisting layer, and the second electrode are the same as those set forth above.

[0211] The formation of the electrode / hole assisting layer / electron assisting layer is not particularly limited and may be appropriately selected in consideration of materials, thickness of the electrode / layer to be prepared, etc. The formation may be performed via a solution process, a (physical or chemical) deposition process, or a combination thereof.

[0212] The formation of the emission layer may be carried out as follows: obtaining a composition comprising the quantum dots and an organic solvent, and applying or depositing the composition on a substrate, an electrode, or a charge-assisting layer (for example, by spin coating, inkjet printing, or contact printing). The formation of the emission layer may include heat treating the applied or deposited quantum dot layer. The temperature for the heat treatment is not particularly limited and may be appropriately selected in consideration of the boiling point of the organic solvent. In one embodiment, the heat treatment may be carried out at a temperature greater than or equal to about 60°C. The organic solvent used for the composition is not particularly limited and may be appropriately selected. In one embodiment, the organic solvent may include a (substituted or unsubstituted) aliphatic hydrocarbon organic solvent, a (substituted or unsubstituted) aromatic hydrocarbon organic solvent, an acetate solvent, or a combination thereof.

[0213] The formation of the emission layer may be performed by preparing an ink composition including the above-mentioned quantum dots of the embodiment and a liquid vehicle, and depositing the prepared ink composition (eg, via an inkjet printing method). Therefore, one embodiment relates to an ink composition including the above-mentioned quantum dots and a liquid vehicle.

[0214] The ink composition may further include light diffusing particles, a binder (e.g., a binder having a carboxylic acid group), and optionally at least one additive (e.g., a photopolymerizable monomer (e.g., a monomer having a carbon-carbon double bond), a crosslinking agent, an initiator (e.g., a photoinitiator), a thiol compound, etc.). The light diffusing particles may include TiO 2 、SiO 2 、BaTiO 3 , ZnO, or a combination thereof. The light diffusing particles may have a size greater than or equal to about 100 nm and less than or equal to about 1 μm.

[0215] The liquid carrier may include an organic solvent. The organic solvent may include a hydrophilic (or water-miscible) organic solvent. The organic solvent may include a hydrophobic organic solvent. The organic solvent may include a polar (organic) solvent. The organic solvent may include a non-polar (organic) solvent.

[0216] The type and amount of the organic solvent may be appropriately selected in consideration of the types and amounts of the above-mentioned main components (ie, the quantum dots, the binder containing a COOH group, the photopolymerizable monomer, the crosslinking agent, the initiator, and the thiol compound if used).

[0217] Non-limiting examples of the liquid carrier may include, but are not limited to: ethyl 3-ethoxypropionate; ethylene glycol series such as ethylene glycol, diethylene glycol, or polyethylene glycol; glycol ethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monomethyl ether, ethylene glycol diethyl ether, or diethylene glycol dimethyl ether; glycol ether acetates such as ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, diethylene glycol monoethyl ether acetate, or diethylene glycol monobutyl ether acetate; propylene glycol series such as propylene glycol; propylene glycol ethers such as propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, propylene glycol dimethyl ether, dipropylene glycol dimethyl ether, ...ethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, propylene glycol dimethyl ether, dipropylene glycol dimethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, diethylene glycol monoethyl ether, diethylene glycol monoethyl ether, propylene glycol monobutyl ether, propylene glycol dimethyl ether, dipropylene glycol dimethyl ether, propylene glycol glycol diethyl ether, or dipropylene glycol diethyl ether; propylene glycol ether acetates such as propylene glycol monomethyl ether acetate or dipropylene glycol monoethyl ether acetate; amides such as N-methylpyrrolidone, dimethylformamide, or dimethylacetamide; ketones such as methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK), or cyclohexanone; petroleum products such as toluene, xylene, or solvent naphtha; esters such as ethyl acetate, propyl acetate, butyl acetate, cyclohexyl acetate, or ethyl lactate; ethers such as diethyl ether, dipropyl ether, or dibutyl ether; (unsubstituted or substituted, such as halogen or chlorine substituted) aliphatic, alicyclic, or aromatic hydrocarbons or their carboxylic acid ester / ester derivatives (e.g., cyclohexyl acetate, etc.); or combinations thereof.

[0218] The components included in the ink composition and their concentrations may be adjusted to control the viscosity of the ink composition, which is not particularly limited. The viscosity of the ink composition may be less than or equal to about 20 centipoise (cP), less than or equal to about 15 cP, less than or equal to about 10 cP, less than or equal to about 5 cP, less than or equal to about 4 cP, less than or equal to about 3 cP, less than or equal to about 2 cP, or less than or equal to about 1.5 cP. The viscosity of the ink composition may be greater than or equal to about 0.1 cP, greater than or equal to about 0.5 cP, or greater than or equal to about 0.8 cP.

[0219] An electroluminescent device including quantum dots of an embodiment can achieve an improved level of EQE and an increased brightness. In an embodiment, the electroluminescent device can have an EQE of greater than or equal to about 9%, greater than or equal to about 9.5%, greater than or equal to about 10%, greater than or equal to about 10.5%, greater than or equal to about 11%, or greater than or equal to about 11.5%. The EQE of the electroluminescent device can be less than or equal to about 30%, but is not limited thereto.

[0220] In one embodiment, the electroluminescent device may have a brightness greater than or equal to about 10,000 cd / m 2 , greater than or equal to approximately 11,000 cd / m 2 , greater than or equal to approximately 12,000 cd / m 2 , greater than or equal to approximately 13,000 cd / m 2 , greater than or equal to approximately 14,000 cd / m 2 , greater than or equal to approximately 15,000 cd / m 2 , greater than or equal to approximately 20,000 cd / m 2 , greater than or equal to approximately 25,000 cd / m 2 , greater than or equal to approximately 30,000 cd / m 2 , greater than or equal to approximately 35,000 cd / m 2 , or greater than or equal to about 40,000 cd / m 2 The brightness of the electroluminescent device may be less than or equal to about 500,000 cd / m 2 , but not limited to this.

[0221] In one embodiment, the electroluminescent device can exhibit an extended lifetime. In one embodiment, the electroluminescent device has a T 50 It may be greater than about 10 hours, greater than or equal to about 15 hours, greater than or equal to about 20 hours, greater than or equal to about 25 hours, or greater than or equal to about 30 hours.

[0222] In one embodiment, an electronic device (equipment) includes the above-mentioned quantum dots. The device (equipment) may include a display device, a light emitting diode (LED), an organic light emitting diode (OLED), a quantum dot LED, a sensor, a solar cell, an image sensor, or a liquid crystal display (LCD), but is not limited thereto. In one embodiment, the electronic device may include a photoluminescent device (e.g., a quantum dot sheet or a lighting device such as a quantum dot track or a liquid crystal display (LCD)). In one embodiment, the electronic device may include a quantum dot sheet and the above-mentioned quantum dots are dispersed in the sheet (e.g., in the form of a quantum dot polymer composite).

[0223] Hereinafter, the embodiments are described in more detail with reference to Examples. However, these Examples are exemplary, and the present scope is not limited thereto.

[0224] Example

[0225] Analytical methods

[0226] 1. Ultraviolet-visible (UV-Vis) spectroscopy analysis

[0227] Ultraviolet (UV) spectroscopy analysis and UV-visible absorption spectra were obtained using a Hitachi U-3310 spectrometer.

[0228] 2. Photoluminescence Analysis

[0229] The photoluminescence (PL) spectra of the prepared nanocrystals were obtained using a Hitachi F-7000 spectrometer at a radiation wavelength of 450 nanometers (nm).

[0230] 3.TEM analysis

[0231] Transmission electron microscopy (TEM) images of the nanocrystals were obtained using a UT F30 Tecnai electron microscope.

[0232] 4. X-ray diffraction (XRD) analysis

[0233] XRD analysis was performed using a Philips XPert PRO instrument with a power of 3 kilowatts (kW).

[0234] 5. Electroluminescence spectroscopy analysis

[0235] A Keithley 2635B source meter was used to measure a current depending on a voltage while applying a voltage and a CS2000 spectrometer was used to measure the electroluminescence (EL) emission brightness.

[0236] Unless specifically mentioned, the synthesis was carried out under an inert atmosphere (nitrogen flowing condition).

[0237] 6.ICP-AES analysis

[0238] Inductively coupled plasma-atomic emission spectrometry (ICP-AES) analysis was performed using Shimadzu ICPS-8100.

[0239] Reference Example 1: An InP core was prepared in the following manner.

[0240] Indium acetate and palmitic acid were dissolved in 1-octadecene in a 200 mL reaction flask and heated at 120° C. under vacuum. The molar ratio of indium to palmitic acid was 1:3. The atmosphere in the flask was heated with N 2 After the reaction flask was heated to 280°C, tri(trimethylsilyl)phosphine (TMS 3 The mixture of TMS and trioctylphosphine (TOP) was added to the mixture, and the reaction was carried out for 20 minutes. The reaction mixture was then cooled to room temperature quickly and acetone was added thereto to produce nanocrystals, which were then separated by centrifugation and dispersed in toluene to obtain a toluene dispersion of InP nanocrystal cores. For every 1 mole of indium, TMS 3 The amount of P was about 0.5 mol. The size of the InP core thus obtained was about 3.3 nm.

[0241] Reference Example 2: Synthesis of Zn Metal Oxide Nanoparticles

[0242] Zinc acetate dihydrate and magnesium acetate tetrahydrate were added to a reactor including dimethyl sulfoxide to provide a molar ratio according to the following chemical formula, and heated at 60° C. in an air atmosphere. (Molar ratio between zinc and magnesium = 0.85:0.15) Subsequently, an ethanol solution of tetramethylammonium hydroxide pentahydrate was added to the reactor dropwise at a rate of 3 milliliters (mL) / minute (mL / min). After stirring it, the obtained Zn 1-x Mg x O (hereinafter, ZnMgO) nanoparticles were centrifuged and dispersed in ethanol.

[0243] The obtained nanoparticles were subjected to X-ray diffraction analysis, thus confirming that they included a crystalline structure. The obtained nanoparticles were analyzed by transmission electron microscopy analysis, and the results showed that the particles had an average size of about 3 nm.

[0244] Embodiment 1:

[0245] Selenium and sulfur were dispersed in trioctylphosphine (TOP) to obtain Se / TOP stock solution and S / TOP stock solution, respectively.

[0246] In a 200 mL reaction flask, zinc acetate and oleic acid were dissolved in trioctylamine and the resulting solution was subjected to vacuum at 120° C. for 10 minutes. The atmosphere in the flask was heated with N 2 While the resulting solution was heated to about 180° C., the toluene dispersion of the InP semiconductor nanocrystal cores was injected therein.

[0247] The resulting mixture was heated to 280° C. and the Se / TOP stock solution was injected into the reaction flask and reacted, and then the reaction temperature was raised to 320° C. again, and the Se / TOP stock solution was injected again to react, thereby forming a ZnSe shell on the InP core. Then, the S / TOP stock solution was added to the reaction system to react to form a ZnS shell on the ZnSe shell.

[0248] The total reaction time for forming the ZnSe shell was 60 minutes and the total amount of selenium used was about 20 moles per 1 mole of indium. The total reaction time for forming the ZnS shell was 60 minutes and the total amount of sulfur used was about 10 moles per 1 mole of indium.

[0249] The final reaction mixture including the obtained InP / ZnSe / ZnS core / shell semiconductor nanocrystals was added with an excess of ethanol and then centrifuged. After centrifugation, the supernatant was discarded and the precipitate was dried and dispersed in chloroform to obtain a quantum dot solution (hereinafter, QD solution).

[0250] (2) For the obtained QD solution, ICP-AES analysis was performed and the results are shown in Table 1. The QD solution was subjected to UV-Vis absorption spectrum analysis and photoluminescence spectrum analysis, and the results are shown in Figure 4 and Table 1. The QDs were subjected to TEM analysis to obtain their average particle size, and the results are shown together in Table 1.

[0251] Embodiment 2:

[0252] InP / ZnSe / ZnS quantum dots were prepared in the same manner as described in Example 1, except that the amounts of the Se precursor and the S precursor used were 25 mol and 15 mol, respectively, relative to 1 mol of indium.

[0253] For the obtained QD solution, ICP-AES analysis was performed and the results are shown in Table 1. UV-Vis absorption spectrum analysis and photoluminescence spectrum analysis were performed on the QD solution, and the results are shown in Table 1. TEM analysis was performed on the QD to obtain its average particle size, and the results are shown together in Table 1.

[0254] Embodiment 3:

[0255] InP / ZnSe / ZnS quantum dots were prepared in the same manner as described in Example 1, except that the amounts of the Se precursor and the S precursor used were 30 mol and 20 mol, respectively, relative to 1 mol of indium.

[0256] For the obtained QD solution, ICP-AES analysis was performed and the results are shown in Table 1. UV-Vis absorption spectrum analysis and photoluminescence spectrum analysis were performed on the QD solution, and the results are shown in Table 1. TEM analysis was performed on the QD to obtain its average particle size, and the results are shown together in Table 1.

[0257] Comparative Example 1:

[0258] InP / ZnSe / ZnS quantum dots were prepared in the same manner as described in Example 1, except that the amount of Se precursor used was 20 moles relative to 1 mole of indium and the temperature for forming the ZnSe shell was always 320°C.

[0259] For the obtained QD solution, ICP-AES analysis was performed and the results are shown in Table 1. UV-Vis absorption spectrum analysis and photoluminescence spectrum analysis were performed on the QD solution, and the results are shown in Table 1. TEM analysis was performed on the QD to obtain its average particle size, and the results are shown together in Table 1.

[0260] Comparative Example 2:

[0261] InP / ZnSe / ZnS quantum dots were prepared in the same manner as described in Example 1, except that the amounts of Se precursor and S precursor used were 10 mol and 5 mol, respectively, relative to 1 mol of indium, and the temperature for forming the ZnSe shell was always 320°C.

[0262] For the obtained QD solution, ICP-AES analysis was performed and the results are shown in Table 1. UV-Vis absorption spectrum analysis and photoluminescence spectrum analysis were performed on the QD solution, and the results are shown in Table 1. TEM analysis was performed on the QD to obtain its average particle size, and the results are shown together in Table 1.

[0263] Table 1

[0264]

[0265] Stokes shift = PL peak wavelength (nm) – first UV absorption peak wavelength (nm)

[0266] Embodiment 4:

[0267] An electroluminescent device having a structure of indium tin oxide (ITO) / poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) (35 nm) / poly(9,9-dioctyl-fluorene-2,7-diyl-co-N-(4-butylphenyl)-diphenylamine) (TFB) (25 nm) / quantum dot emission layer (20 nm) / ZnMgO (40 nm) / Al (100 nm) was prepared as follows.

[0268] The ITO-deposited glass substrate was surface treated with UV-ozone for 15 min, then spin-coated with a PEDOT:PSS solution (HC Starks) and heated at 150 °C for 10 min in an air atmosphere, and then 2 The resulting mixture was heat treated again at 150° C. for 10 minutes under an atmosphere to provide a hole injection layer having a thickness of 35 nm.

[0269] Subsequently, a poly[(9,9-dioctylfluorene-2,7-diyl)-co-(N-(4-butylphenyl)diphenylamine)] solution (TFB) (Sumitomo) was spin-coated on the hole injection layer and heat-treated at 150° C. for 30 minutes to form a hole transport layer.

[0270] The core / shell quantum dot solution obtained from Example 1 was spin-coated on the hole transport layer and heat-treated at 80° C. for 30 minutes to form a quantum dot emission layer.

[0271] A solution of ZnMgO nanoparticles according to Reference Example 2 was prepared (solvent: ethanol, optical density: 0.5 arbitrary unit). The solution was spin-coated on the quantum dot emission layer and heat-treated at 80° C. for 30 minutes to form an electron assisting layer. On the surface of the electron assisting layer, aluminum (Al) was vacuum-deposited to form a second electrode.

[0272] The electroluminescent properties of the obtained quantum dot light-emitting device were evaluated using a Keithley 2200 source measurement device and a Minolta CS2000 spectroradiometer (current-voltage-brightness measurement device). The current, brightness, and electroluminescence (EL) depending on the voltage applied to the device were measured by the current-voltage-brightness measurement device, and the external quantum efficiency was calculated from this. The results are shown in Table 2, and Figure 5 and 6 middle.

[0273] Embodiment 5:

[0274] An electroluminescent device was manufactured in the same manner as described in Example 4, except that the quantum dots of Example 2 were used.

[0275] The electroluminescent properties of the obtained quantum dot light emitting device were evaluated using a Keithley 2200 source measurement device and a Minolta CS2000 spectroradiometer (current-voltage-brightness measurement device). The current, brightness, and electroluminescence (EL) depending on the voltage applied to the device were measured by the current-voltage-brightness measurement device, and the external quantum efficiency was calculated from this. The results are shown in Table 2.

[0276] Comparative Example 3:

[0277] An electroluminescent device was manufactured in the same manner as described in Example 4, except that the quantum dots of Comparative Example 2 were used.

[0278] The electroluminescent properties of the obtained quantum dot light emitting device were evaluated using a Keithley 2200 source measurement device and a Minolta CS2000 spectroradiometer (current-voltage-brightness measurement device). The current, brightness, and electroluminescence (EL) depending on the voltage applied to the device were measured by the current-voltage-brightness measurement device, and the external quantum efficiency was calculated from this. The results are shown in Table 2.

[0279] Comparative Example 4:

[0280] An electroluminescent device was manufactured in the same manner as described in Example 4, except that the quantum dots of Comparative Example 2 were used and a triaryltriazine compound was used instead of zinc metal oxide particles to form the organic ETL.

[0281] The electroluminescent properties of the obtained quantum dot light emitting device were evaluated using a Keithley 2200 source measurement device and a Minolta CS2000 spectroradiometer (current-voltage-brightness measurement device). The current, brightness, and electroluminescence (EL) depending on the voltage applied to the device were measured by the current-voltage-brightness measurement device, and the external quantum efficiency was calculated from this. The results are shown in Table 2.

[0282] Table 2

[0283]

[0284] T 50 Lifespan (h): When the device is at 100 nits (cd / m 2 The time it takes for the brightness of a device to decrease to 50% of its initial value (100%) when operating at

[0285] The results of Table 2 demonstrate that the electroluminescent devices of the Examples (including quantum dots) can exhibit improved electroluminescent properties and lifetimes compared to the devices of the Comparative Examples.

[0286] Example 6: (Example 1 QD + organic ETL)

[0287] An electroluminescent device was manufactured in the same manner as described in Example 4, except that a triaryltriazine compound was used instead of zinc metal oxide particles to form the organic ETL.

[0288] The electroluminescent properties of the obtained quantum dot light-emitting device were evaluated using a Keithley 2200 source measurement device and a Minolta CS2000 spectroradiometer (current-voltage-brightness measurement device). The current, brightness, and electroluminescence (EL) depending on the voltage applied to the device were measured by the current-voltage-brightness measurement device, and the external quantum efficiency was calculated therefrom. The results confirmed that the device of Example 6 can present an improved EQE and brightness increased to more than 3 times and more than 6 times, respectively, compared to the device of Comparative Example 4.

[0289] Example 7: (Example 2 QD + organic ETL)

[0290] An electroluminescent device was manufactured in the same manner as set forth in Example 4, except that the quantum dots of Example 2 were used and a triaryltriazine compound was used instead of zinc metal oxide particles to form the organic ETL.

[0291] The electroluminescent properties of the obtained quantum dot light-emitting device were evaluated using a Keithley 2200 source measurement device and a Minolta CS2000 spectroradiometer (current-voltage-brightness measurement device). The current, brightness, and electroluminescence (EL) depending on the voltage applied to the device were measured by the current-voltage-brightness measurement device, and the external quantum efficiency was calculated therefrom. The results confirmed that the device of Example 7 can present an improved EQE and brightness increased to more than 3 times and more than 10 times, respectively, compared to the device of Comparative Example 4.

[0292] While the disclosure has been described in connection with what are presently considered to be practical example embodiments, it is to be understood that the invention is not limited to the disclosed embodiments, but on the contrary is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.

[0293] Description of Reference Numerals

[0294] 10: Light-emitting devices

[0295] 11: First electrode

[0296] 11a: Anode

[0297] 12, 20: Hole auxiliary layer

[0298] 13,30: Emission layer

[0299] 14, 40: Electronic auxiliary layer

[0300] 15: Second electrode

[0301] 15a: cathode

[0302] 100: Transparent substrate

Claims

1. An electroluminescent device comprising a first electrode and a second electrode facing each other, an emission layer disposed between the first electrode and the second electrode, the emission layer comprising quantum dots, and The quantum dots include A semiconductor nanocrystal core comprising indium and phosphorus, a first semiconductor nanocrystal shell disposed on the semiconductor nanocrystal core, the first semiconductor nanocrystal shell comprising zinc and selenium, and a second semiconductor nanocrystalline shell disposed on the first semiconductor nanocrystalline shell, the second semiconductor nanocrystalline shell comprising zinc and sulfur, wherein the quantum dots do not include cadmium, The electroluminescent device has an external quantum efficiency greater than or equal to 9% and a light emission efficiency greater than or equal to 10,000 candela / square meter (cd / m 2 ) at maximum brightness, and In the quantum dots, the molar ratio of indium to the sum of sulfur and selenium, In:(Se+S), is less than 0.05:

1. 2 . The electroluminescent device according to claim 1 , wherein the wavelength of the maximum photoluminescence peak of the quantum dot exists in the range of greater than or equal to 600 nanometers and less than or equal to 650 nanometers.

3. The electroluminescent device of claim 1, wherein the average particle size of the quantum dots is greater than or equal to 8 nanometers. The electroluminescent device of claim 1 , wherein the average particle size of the quantum dots is greater than or equal to 9 nanometers. The electroluminescent device of claim 1 , wherein the quantum yield of the quantum dots is greater than or equal to 60%.

6. The electroluminescent device of claim 3, wherein the standard deviation of the particle size distribution of the quantum dots is less than or equal to 20% of the average size thereof.

7. The electroluminescent device of claim 1, wherein in the quantum dots, a molar ratio of indium to the sum of sulfur and selenium, In:(Se+S), is greater than or equal to 0.02:1 and less than 0.05:

1.

8. The electroluminescent device of claim 1, wherein in the quantum dots, a molar ratio of sulfur to selenium, S:Se, is greater than or equal to 0.01:1 and less than or equal to 4.5:

1.

9. The electroluminescent device of claim 1, wherein the first semiconductor nanocrystal shell is disposed directly on a surface of the semiconductor nanocrystal core and the first semiconductor nanocrystal shell does not include sulfur.

10. The electroluminescent device of claim 9, wherein the first semiconductor nanocrystal shell has a thickness greater than or equal to 6 monolayers.

11. The electroluminescent device of claim 9, wherein the second semiconductor nanocrystalline shell is the outermost layer of the quantum dot and the second semiconductor nanocrystalline shell is disposed directly on a surface of the first semiconductor nanocrystalline shell.

12. The electroluminescent device of claim 1, wherein the difference between the maximum photoluminescence peak wavelength and the first absorption peak wavelength of the quantum dot is less than or equal to 16 nanometers.

13. The electroluminescent device of claim 1, wherein the electroluminescent device comprises an electron transport layer between the second electrode and the emissive layer.

14. The electroluminescent device of claim 13, wherein the electron transport layer comprises a metal oxide comprising zinc.

15. The electroluminescent device of claim 14, wherein the metal oxide comprises Zn 1-x M x O, wherein M is Mg, Ca, Zr, W, Li, Y, Al, Ti, or a combination thereof, and 0≤x≤0.

5.

16. Quantum dots comprising A semiconductor nanocrystal core comprising indium and phosphorus, a first semiconductor nanocrystal shell disposed on the semiconductor nanocrystal core, the first semiconductor nanocrystal shell comprising zinc and selenium, and a second semiconductor nanocrystalline shell disposed on the first semiconductor nanocrystalline shell, the second semiconductor nanocrystalline shell comprising zinc and sulfur, wherein the quantum dots do not include cadmium, wherein the difference between the maximum photoluminescence peak wavelength and the first absorption peak wavelength of the quantum dot is less than or equal to 20 nanometers, and In the quantum dots, the molar ratio of indium to the sum of sulfur and selenium, In:(Se+S), is less than 0.05:

1.

17. The quantum dots of claim 16, wherein the average particle size of the quantum dots is greater than or equal to 8 nanometers and the standard deviation of the particle size distribution of the quantum dots is less than or equal to 20% of the average particle size. 18 . The quantum dot of claim 16 , wherein in the quantum dot, a molar ratio of indium to the sum of sulfur and selenium, In / (Se+S), is greater than or equal to 0.02:1 and less than 0.05:

1.

19. The quantum dot of claim 16, wherein the first semiconductor nanocrystal shell is disposed directly on a surface of the semiconductor nanocrystal core and the first semiconductor nanocrystal shell does not include sulfur, and the second semiconductor nanocrystal shell is the outermost layer of the quantum dot.

20. The quantum dot of claim 19, wherein the first semiconductor nanocrystal shell has a thickness greater than or equal to 6 monolayers.

21. The quantum dot of claim 16, wherein the difference between the maximum photoluminescence peak wavelength and the first absorption peak wavelength of the quantum dot is less than or equal to 17 nanometers.

22. The quantum dots of claim 16, wherein an average particle size of the quantum dots is greater than or equal to 8 nanometers and less than or equal to 50 nm.

23. A composition comprising an organic solvent and the quantum dots according to any one of claims 16 to 22.

Citation Information

Patent Citations

  • Fan-out semiconductor package and package on package device comprising the same

    KR1020180102972A

  • Anistropic semiconductor nanoparticles

    CN103154183A

  • Highly lumminescent nanostructures and methods of producing same

    CN104520228A

  • Composite nanoparticles including a phthalic acid derivative

    CN105829494A